2013
DOI: 10.1007/s12016-013-8371-1
|View full text |Cite
|
Sign up to set email alerts
|

Volatile Substance Misuse: An Updated Review of Toxicity and Treatment

Abstract: Educational campaigns and legislative actions may have led to an overall decrease in the prevalence of volatile substance misuse (VSM) in many countries; however, it is still a common practice throughout the world. Studies currently suggest that girls are misusing volatile substances more than before and at a prevalence rate equal to or exceeding that of boys in several countries. Products that may be misused are ubiquitous and relatively easy to acquire. The most commonly misused substances in recent studies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0
7

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 153 publications
0
12
0
7
Order By: Relevance
“…Volatile substance misuse, especially among the youth, is an alarming social problem in many countries [1]. It is reported that among the misused volatile substances, butane misuse has the highest fatality rate [2].…”
Section: Introductionmentioning
confidence: 99%
“…Volatile substance misuse, especially among the youth, is an alarming social problem in many countries [1]. It is reported that among the misused volatile substances, butane misuse has the highest fatality rate [2].…”
Section: Introductionmentioning
confidence: 99%
“…3 Em particular, o tolueno é um composto orgânico encontrado em combustíveis, tintas, colas e esmaltes. 4 Desta forma, a contaminação de água por tolueno pode ser considerada um problema ambiental frequente.…”
Section: Introductionunclassified
“…There are reported cases of ventricular fibrillation in patients misusing butane [5], and both propane and butane are reported to precipitate fatal arrhythmias through the stimulation of the vagus nerve [6]. Moreover several fatal intoxications due to butane [7], propane [6] or mixtures containing both propane and butane [8][9] are reported.…”
Section: Introductionmentioning
confidence: 99%